AN ISLAMIC COUNSELING SERVICES IN MANAGEMENT STRESS LEARNING STUDENTS CLASS XI SENIOR HIGH SCHOOL - Frastika Agatha (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2020)
The problem in this study is Islamic counseling services in tackling stress learning students class XI SMA Negeri 1 Selesai in years lesson 2018/2019. This research aims to know the stress of learning students inside or outside the classroom. Methodologically, this research is a qualitative phenomenological study. The methods used in data collection are observations, interviews and documentation. To analyze data, researchers use qualitative analysis with data exposure measures, data reduction and withdrawal of conclusions. The results of the study is stressful condition of students have improved enough, the implementation of Islamic counseling conducted by BK teachers has been running with maximum, Islamic counseling services in tackling the stress of learning students class XI SMA Negeri 1 Selesaifully run effectively.